If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6f + 1 = (5f + -2) Reorder the terms: 1 + 6f = (5f + -2) Reorder the terms: 1 + 6f = (-2 + 5f) Remove parenthesis around (-2 + 5f) 1 + 6f = -2 + 5f Solving 1 + 6f = -2 + 5f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-5f' to each side of the equation. 1 + 6f + -5f = -2 + 5f + -5f Combine like terms: 6f + -5f = 1f 1 + 1f = -2 + 5f + -5f Combine like terms: 5f + -5f = 0 1 + 1f = -2 + 0 1 + 1f = -2 Add '-1' to each side of the equation. 1 + -1 + 1f = -2 + -1 Combine like terms: 1 + -1 = 0 0 + 1f = -2 + -1 1f = -2 + -1 Combine like terms: -2 + -1 = -3 1f = -3 Divide each side by '1'. f = -3 Simplifying f = -3
| 5(x+3)-3x+7= | | -17x+9x-245=171 | | 0=12z | | 3(b-21)=27-3(b-4) | | 13/3-x/4=3x | | x^2-9x*y-36y^2=0 | | -2x-87=-10x+73 | | y=350(1+0.75) | | 17=b-7 | | 11x+8=3x-7 | | (8y+7x)-(-11y-2x)=3y+5 | | -40-7x=32-11x | | f(x)=x^3-8x^2+16x | | x^2-5x*y-50y^2=0 | | (b+7)(b-4)= | | 5x+4-3x+9= | | 6x+3+y+x+2x+1=241 | | 7x-46=22+3x | | 16-8-x-13=72x+15x+15 | | 48-n=7-4 | | P=c+b+2aforc | | 2x-17=x+7 | | 5y+21+7y-1=180 | | 2/7(5x+4)=1/2(3x-22)+10 | | 3x^2-4y^3= | | 6x+1-12x=2x+4 | | Log(x-2)+log(x+2)=log*3x | | x^2-14x*y-32y^2=0 | | -9(v+4)+4v+5=7v+8 | | P=c+b+25forc | | 72=-11-r | | -90+3x=-8x+185 |